Role of non-pulmonary vein triggers in persistent atrial fibrillation - So Young Yang; Myung-Jin Cha; Hyeon Jeong Oh; Min Soo Cho; Jun Kim; Gi-Byoung Nam; Kee-Joon Choi (International Journal of Arrhythmia, 2023)
Abstract Pulmonary vein isolation is an well-established treatment strategy for atrial fibrillation (AF), and it is especially effective for patients with paroxysmal AF. However, the success rate is limited for patients with persistent AF, because non-pulmonary vein triggers which increase AF recurrence are frequently found in these patients. The major non-pulmonary vein triggers are from the left atrial posterior wall, left atrial appendage, ligament of Marshall, coronary sinus, superior vena cava, and crista terminalis, but other atrial sites can also generate AF triggers. All these sites have been known to contain atrial myocytes with potential arrhythmogenic electrical activity. The prevalence and clinical characteristics of these non-pulmonary vein triggers are well studied; however, the clinical outcome of catheter ablation for persistent AF is still unclear. Here, we reviewed the current ablation strategies for persistent AF and the clinical implications of major non-pulmonary vein triggers.